Exploring the Representation of Gender in Foklores from Central Kalimantan - Wulandari, Indah; Sujiyani, Erma; Retsi, Olga Dona; Susanty, Susanty (The Study Program of English Education of Palangka Raya University, 2025)
Folklores are frequently used as teaching media at schools. However, they are suspected to contain gender stereotypes. This study aims to examine the gender representation and gender stereotypes in 28 folklores from Central Kalimantan published in two books by the Ministry of Education and Culture of the Republic of Indonesia in 1982 and 1995. Gender representation is explored through the roles and occurrence of the characters in the folklores, while four categories of gender stereotypes (personality traits, domestic behaviors, occupations, and physical appearances) are used to investigate the gender stereotypes attached to the male and female characters in the stories. The results show there is an imbalanced representation of male and female characters in Central Kalimantan folklores; from the total of 106 characters, male representation has almost twice in occurrence (60.4%) compared to the female one (39.6%). Mostly, males are the main characters in the stories having both positive or negative roles, and the females have only inferior roles. The gender stereotypes of patriarchy are found to be promoted through the characters’ description in the folklores. Therefore, to represent the proper concept of gender equality through stories, a critical view is needed in selecting folklores as teaching media at schools.